Multiwavelength Brillouin erbium fiber laser in virtual linear cavity - Al-Alimi, Abdulmoghni Ali Wazea (IEEE, 2012)
A multiple wavelength Brillouin/erbium fiber laser in a virtual linear cavity configuration is demonstrated. The virtual linear cavity is formed by utilizing a double pass amplification box at one end of the cavity, and a virtual mirror on the other end. The virtual mirror is created by the stimulated Brillouin scattering (SBS) effect in standard single mode fiber. The tunability limitation of conventional MWBEFLs is eliminated by using half mirrorless linear cavity technique. Due to the large amount of gain achieved by the double pass amplification box, 7 Stokes lines are achieved at pump power and Brillouin pump power of 130 mW And 0 dBm, respectively. Up to 4 channels can be freely tuned over a tuning range of 37.5 nm from 1530 nm 1567 nm.